2016
DOI: 10.1016/j.jhep.2016.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Phase I open label liver-directed gene therapy clinical trial for acute intermittent porphyria

Abstract: The observational phase was registered at Clinicaltrial.gov as NCT 02076763. The interventional phase study was registered at EudraCT as n° 2011-005590-23 and at Clinicaltrial.gov as NCT02082860.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
99
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(99 citation statements)
references
References 33 publications
0
99
0
Order By: Relevance
“…Aside from the treatment of hemophilia, this is a potentially attractive feature of exo-AAV, which may be useful for applications like promoterless AAV, 33 or any application of gene transfer in which high levels of hepatocyte targeting are needed. 34 Of note, one advantage of combining exosomes with AAV vectors, as opposed to using exosomes to carry naked plasmid DNA, resides in the long-lived transgene expression that can be obtained with AAV vectors in liver. 2,35 Additionally, we have previously demonstrated that producing exo-AAV in the absence of capsid does not lead to detectable transduction, at least in cultured cells.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from the treatment of hemophilia, this is a potentially attractive feature of exo-AAV, which may be useful for applications like promoterless AAV, 33 or any application of gene transfer in which high levels of hepatocyte targeting are needed. 34 Of note, one advantage of combining exosomes with AAV vectors, as opposed to using exosomes to carry naked plasmid DNA, resides in the long-lived transgene expression that can be obtained with AAV vectors in liver. 2,35 Additionally, we have previously demonstrated that producing exo-AAV in the absence of capsid does not lead to detectable transduction, at least in cultured cells.…”
Section: Discussionmentioning
confidence: 99%
“…Also, because the frequency of acute attacks in AIP patients is highly variable and can change in the absence of identifiable factors, the clinical data from this trial should be taken as an additional aspect of the safety of the treatment. This study provided important data regarding the safety of AAV5 vectors for human gene therapy and has major implications for the design of future intervention studies [39]. In contrast to what has been observed with AAV-2 and -8 vectors used for the treatment of hemophilia [40,41], AAV-5 vector did not elicit cellular immune responses.…”
Section: Article Highlightsmentioning
confidence: 77%
“…While two patients, both receiving low doses of vector, experienced a significant clinical improvement, the beneficial effect on the rest of the patients was not so clear. However, most of the participants in the study scored better in psychometric tests following therapy [39]. It could be speculated that the different genetic backgrounds among patients result in different endogenous PBGD activity and may be the reason of this heterogeneity.…”
Section: Expert Opinionmentioning
confidence: 87%
See 2 more Smart Citations